Some Sharp Estimates for Convex Hypersurfaces of Pinched Normal Curvature - Drach, K. (Журнал математической физики, анализа, геометрии, 2015)
For a convex domain D bounded by the hypersurface ∂D in a space of constant curvature we give sharp bounds on the width R - r of a spherical shell with radii R and r that can enclose ∂D, provided that normal curvatures of ∂D are pinched by two positive constants. Furthermore, in the Euclidean case we also present sharp estimates for the quotient R/r. From the obtained estimates we derive stability results for almost umbilical hypersurfaces in the constant curvature spaces. В пространствах постоянной кривизны получены точные оценки для ширины R — r сферического слоя с радиусами R и r, в который можно поместить гиперповерхность ∂D, ограничивающую выпуклую область D, при учете, что нормальные кривизны ∂D зажаты между двумя положительными константами. В евклидовом случае также приведена точная оценка для отношения R/r. Из найденных оценок получены результаты по устойчивости почти омбилических гиперповерхностей в пространствах постоянной кривизны. У просторах сталої кривини отримано точні оцінки для ширини R — r сферичного шару з радіусами R та r, в який можна помістити гіперповерхнго ∂D, що обмежує опуклу область D, за умови, що нормалвні кривини ∂D, зажаті між двома додатними константами. У випадку евклідового простору також наведена точна оцінка для відношення R/r. 3 оцінок, що були знайдені, отримано результати зі стійкості майже омбілічних гіперповерхонв у просторах сталої кривини.